2023
DOI: 10.1186/s12891-023-06261-9
|View full text |Cite
|
Sign up to set email alerts
|

Determining minimal important differences for patient-reported outcome measures in shoulder, lateral elbow, patellar and Achilles tendinopathies using distribution-based methods

Abstract: Background Minimal important difference (MID) is a concept used inconsistently and arbitrarily in tendinopathy research. Our aim was to determine the MIDs for the most commonly used tendinopathy outcome measures using data-driven approaches. Methods Recently published systematic reviews of randomised controlled trials (RCTs) on tendinopathy management were identified and used for extraction of eligible studies through a literature search. Each elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…This is larger than the MDC for the VISA-A, which is reported as between 7.8 to 8.2. 34 A study using an anchor-based method in the VISA-A reported the MCID as 14 units, 35 which is comparable to our estimated measure. Another study using the VISA-A estimated the MCID to be 6.5 units, however this was estimated from a selective sample of 15 participants with insertional Achilles tendinopathy, which may also explain the smaller MCID.…”
Section: Discussionsupporting
confidence: 78%
“…This is larger than the MDC for the VISA-A, which is reported as between 7.8 to 8.2. 34 A study using an anchor-based method in the VISA-A reported the MCID as 14 units, 35 which is comparable to our estimated measure. Another study using the VISA-A estimated the MCID to be 6.5 units, however this was estimated from a selective sample of 15 participants with insertional Achilles tendinopathy, which may also explain the smaller MCID.…”
Section: Discussionsupporting
confidence: 78%
“…However, a secondary post hoc sample size calculation with G*Power (v3.1.9.2, Heinrich-Heine-University, Dusseldorf, Germany) revealed the feasible sample size for a mixed model RM-ANOVA with three groups (no-sham group, single-sham group, and double-sham group) participating in four experimental sessions. With a power of 90% and an alpha level of 0.01, a total of 42 participants (14 per group) were needed for participation to detect the minimal important difference of 1.2 points (partial η 2 = 0.05) in the Visual Analogue Scale ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, when evaluating centrifuge duration as a factor for PRP preparation, marginally greater VAS reduction and VISA-P improvements were observed in the short centrifuge duration group. However, the difference in both score improvements between long- and short-duration centrifuge cycles was neither statistically significant nor reached minimal clinically important difference values [ 26 ], potentially suggesting that centrifuge duration may not be an important factor in PRP preparation.…”
Section: Reviewmentioning
confidence: 99%